MENINGKATKAN KETERAMPILAN MENULIS STRUKTUR KALIMAT MENGGUNAKAN MEDIA PEMBELAJARAN AUDIO VISUAL PADA SISWA KELAS IV SD NEGERI MUGARSARI KOTA TASIKMALAYA - Indi Rahma Inayatulloh; Riga Zahara Nurani; Fajar Nugraha (STKIP Subang, 2025)
Learning to write sentence structures is a language skill that is productive and expressive. Through writing, someone can communicate, document ideas and events, and develop thinking. The results of interviews with teachers at SDN Mugarsari, precisely in grade 4 of elementary school, showed a problem in learning to write sentence structures from 25 students who completed the KKM only 9 people. So this study aims to improve writing skills using audio-visual learning media on sentence structures. The stages of the study were using the classroom action research (CAR) method which contains stages including planning, implementation and improvement which are divided into several cycles, namely Pre-Cycle, Cycle I, and Cycle II. The results of the study showed that there was an increase in accordance with the indicators of success in sentence structure writing skills. The percentage of improvement in sentence structure writing skills obtained after implementing learning using animated audio-visual media showed clear progress.